Impact of Social Capital on Sharing Human Resources in Science and Technology in Vietnam - Huong, Dinh Thi Thu; Hongjuan, Yang; Khanh, Duong Van (Revista Gestão & Tecnologia, 2024)
This study analyzes the impact of social capital factors such as structural social capital, cognitive social capital, relational social capital, sharing behavior, sharing desire, and sharing capability on the effectiveness of sharing human resources in the field of science and technology in Vietnam. The survey was conducted using a questionnaire to collect data through convenience sampling method. The study collected 478 responses from lecturers and researchers at several universities, research centers, and institutes in Vietnam. The research hypotheses were tested using a multivariate regression model. The findings show that structural social capital, relational social capital, sharing behavior, and sharing capability positively impact the effectiveness of sharing human resources in science and technology. Based on these findings, the study proposes several solutions for developing human resources in science and technology by promoting social capital and knowledge sharing processes.